Lethal effects of an insecticidal spider venom peptide involve positive allosteric modulation of insect nicotinic acetylcholine receptors. (December 2017) - Windley, Monique J.; Vetter, Irina; Lewis, Richard J.; Nicholson, Graham M.
Abstract: κ-Hexatoxins (κ-HXTXs) are a family of excitotoxic insect-selective neurotoxins from Australian funnel-web spiders that are lethal to a wide range of insects, but display no toxicity towards vertebrates. The prototypic κ-HXTX-Hv1c selectively blocks native and expressed cockroach large-conductance calcium-activated potassium (BKCa or KCa 1.1) channels, but not their mammalian orthologs. Despite this potent and selective action on insect KCa 1.1 channels, we found that the classical KCa 1.1 blockers paxilline, charybdotoxin and iberiotoxin, which all block insect KCa 1.1 channels, are not lethal in crickets. We therefore used whole-cell patch-clamp analysis of cockroach dorsal unpaired median (DUM) neurons to study the effects of κ-HXTX-Hv1c on sodium-activated (KNa ), delayed-rectifier (KDR ) and 'A-type' transient (KA ) K + channels. 1 μM κ-HXTX-Hv1c failed to significantly inhibit cockroach KNa and KDR channels, but did cause a 30 ± 7% saturating inhibition of KA channel currents, possibly via a Kv4 (Shal-like) action. However, this modest action at such a high concentration of κ-HXTX-Hv1c would indicate a different lethal target. Accordingly, we assessed the actions of κ-HXTX-Hv1c on neurotransmitter-gated ion channels in cockroach DUM neurons. We found that κ-HXTX-Hv1c failed to produce any major effects on GABAA or glutamate-Cl receptors but dramatically slowed nicotine-evoked ACh receptor (nAChR) current decay and reversed nAChR desensitization. These actions occurred without any alterations to nAChR current amplitude or the nicotine concentration-response curve, and are consistent with a positive allosteric modulation of nAChRs. κ-HXTX-Hv1c therefore represents the first venom peptide that selectively modulates insect nAChRs with a mode of action similar to the excitotoxic insecticide spinosyn A. This article is part of the Special Issue entitled 'Venom-derived Peptides as Pharmacological Tools.' Highlights: The previously characterized BKCa channel block is not responsible for the lethal excitatory toxicity of κ-HXTX-Hv1c. κ-HXTX-Hv1c acts as a positive allosteric modulator of insect nAChRs to prolong current decay and reverse desensitization. The likely lethal target of κ-HXTX-Hv1c is the nAChR, acting by a mechanism similar to that of the insecticide spinosyn A.